RI 3181 Active List Of Permissible Explosives And Blasting Devices Approved Prior To June 30, 1932 - Permissible Explosives Tested Under Schedule 17B (The National Institute for Occupational Safety and Health (NIOSH), 1932)
An active list of permissible explosives was published in July, 1931, as part of United States Bureau of Mines Report of Investigations 313, under the title of "Active List of Permissible Explosives and Blasting Devices Approved Prior to June 30, 1931." Changes in that list were authorized in August, September, October, November, and December, 1931, and. January and March, 1932, as published in Reports of Investigations 3l40, 3147, 3l50, 3155, 3158, 3161, and 3163, respectively. By these changes the following explosives were added to the active permissible list: [Austin Red Diamond No. 1, L. F. Gel-Coalite W. L. F. Austin Red-Diamond No. 5, L., F. Gen-Gel No. 2. Black Diamond Nu-Gel No. 1 Genite C-1 Burton 1, L. F. Liberty No. 4 Burton 2, L. F. Liberty No. 5 Burton 10, L. F. Peerless D Burton 12, L. F. Permigel 1, L. F. Burton F, L. F.]